Association between oxidative balance score with cardiovascular - kidney - metabolic syndrome and all-cause mortality among US population - Lin Shi; Lin Shi; Dan Zhang; Shuangshuang Zhang (Frontiers in Nutrition)
BackgroundCardiovascular-Kidney-Metabolic (CKM) syndrome is a multi-stage condition with significant public health implications. The oxidative balance score (OBS), which integrates dietary and lifestyle pro-oxidants and antioxidants, offers a novel approach for evaluating oxidative stress in relation to CKM stages and outcomes. This study aimed to investigate the association between OBS and advanced CKM stages, as well as its relationship with all-cause mortality in a US population.MethodsData were derived from the National Health and Nutrition Examination Survey. CKM stages were classified based on published criteria, and OBS was calculated using 20 components reflecting oxidative stress balance. Logistic regression and Cox proportional hazards models were applied to evaluate the associations between OBS and advanced CKM stages, and all-cause mortality, respectively. Restricted cubic spline (RCS) analyses were used to assess the potential nonlinear relationships.ResultsA total of 12,793 participants aged 30–79 years were enrolled. A higher OBS was inversely associated with advanced CKM stages (adjusted OR for T3:0.58, 95% CI 0.46–0.73). A significant inverse relationship was also observed between OBS and all-cause mortality across the CKM stages. In non-advanced CKM stages, the adjusted HR for T3 was 0.58 (95% CI 0.40–0.86). In advanced CKM stages, the inverse association persisted (adjusted HR for T3: 0.62, 95% CI 0.43–0.89). RCS analyses confirmed a dose–response relationship between higher OBS and reduced mortality risk.ConclusionThis study highlights the protective role of higher OBS against advanced CKM stages and mortality, suggesting the potential of oxidative stress modulation as a strategy for managing CKM syndrome.